Opioid-Induced Tolerance and Hyperalgesia - Mercadante, Sebastiano; Arcuri, Edoardo; Santoni, Angela (CNS drugs, 2019)
Opioids are very potent and efficacious drugs, traditionally used for both acute and chronic pain conditions. However, the use of opioids is frequently associated with the occurrence of adverse effects or clinical problems. Other than adverse effects and dependence, the development of tolerance is a significant problem, as it requires increased opioid drug doses to achieve the same effect. Mechanisms of opioid tolerance include drug-induced adaptations or allostatic changes at the cellular, circuitry, and system levels. Dose escalation in long-term opioid therapy might cause opioid-induced hyperalgesia (OIH), which is a state of hypersensitivity to painful stimuli associated with opioid therapy, resulting in exacerbation of pain sensation rather than relief of pain. Various strategies may provide extra-opioid analgesia. There are drugs that may produce independent analgesic effects. A tailored treatment provided by skilled personnel, in accordance with the individual condition, is mandatory. Any treatment aimed at reducing opioid consumption may be indicated in these circumstances. Interventional techniques able to decrease the pain input may allow a decrease in the opioid dose, thus reverting the mechanisms producing tolerance of OIH. Intrathecal therapy with local anesthetics and a sympathetic block are the most common techniques utilized in these circumstances.